A Phenomenological Study of Informal Education: Relations between Parents and Children in Family Economic Education - Muhammad Hasan; Nur Arisah; Nurjannah; Andi Tenri Ampa; Tuti Supatminingsih (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This study aims to explore phenomenologically informal education through the role of parents in providing economic education to children and education in family financial management. This study uses a qualitative approach to phenomenology. The informants in this study were six parents who were heads of families and, based on their profiling, met the requirements for achieving the research objectives. Data collection was carried out using interviews, observation, and documentation. Qualitative data analysis techniques are used through the data reduction phase to present information and draw conclusions. Based on the research findings, it can be concluded that parents have the perception that economic education must be taught to children from an early age, especially in terms of managing money, reducing unnecessary expenses, and starting to save from an early age, so that children get used to being intelligent economic beings and prepare for future success. When teaching their children about family economics, parents focus on helping their children understand their family's financial situation and how to act responsibly by only spending as needed by providing explanations and modeling economic behavior. Keywords: Informal Education, Economic Education, Family Financial Management